Epidermodysplasia Verruciformis in Lipoid Proteinosis: Case Report and Discussion of Pathophysiology. Issue 1 (28th March 2013) - O'Blenes, Catherine; Pasternak, Sylvia; Issekutz, Andrew; Gillis, Jane; Chowdhury, Dhiman; Finlayson, Laura
Abstract Lipoid proteinosis (LP) is a rare autosomal recessive genodermatosis caused by mutations in extracellular matrix protein 1 (ECM1) that involves deposition of basement membrane–like material in the skin and other organs. Epidermodysplasia verruciformis (EV) is also a rare autosomal recessive genodermatosis involving susceptibility to human papillomavirus (HPV) infections and squamous cell carcinoma, caused in most cases by homozygous mutations in EVER1 or EVER2. We describe a case of EV in a patient with LP and discuss the pathophysiology. A 3‐year‐old Lebanese girl presented with hoarseness, beaded papules along the eyelid margins, waxy papules and plaques on her head and neck, and lichenoid verrucous papules on the forearms and hands. Histopathology of the waxy papules exhibited deposition of periodic acid Schiff–positive basement membrane–like material in the superficial dermis, characteristic of LP. The verruca plana–like lesions exhibited acanthosis and enlarged keratinocytes with pale blue‐grey cytoplasm and a perinuclear halo, consistent with verrucae and EV. Polymerase chain reaction amplification and sequencing of ECM1, EVER1, and EVER2 demonstrated a homozygous point mutation, c.389C>T (p.Thr130Met), in exon 6 of ECM1 and a heterozygous point mutation, c.917 A>T (p.Asn306Ile), in exon 8 in EVER2, known to cause EV in homozygous patients. The homozygous point mutation c.389C>T in ECM1 may be a novel mutation causing LP. Verruca plana–like lesions seen in LP appear to represent a form of acquired EV. In this patient, a heterozygous mutation in EVER2 at c.917 A>T may also have conferred susceptibility to HPV infection.